Pengawasan Kesehatan Bagi Pilot Di Indonesia - Susanti Susanti (Research and Development Agency of The Ministry of Transportation, 2012)
Pilots in aviation an important role in the safety of passengers while in flight. A case of drug use by a pilot is considerably shocking the aviation world. Drug use by pilots certainly something that can not be tolerated, because pilots are responsibility for the safety of passengers. In an effort to realize comprehensive aviation safety, it required an assessment of health surveillance forms that has been the basis for pilothealth surveillance forms that has been the basis for pilot health appraisal. Analysis were conducted using descriptive method and results show the unavailability of an effective form of health surveillance for pilots due to solely relying on the government’s role as a regulator to secure all aviation safety. It is expected that all parties including the government, privates, society and every flight practitioner will give their support.Pilot dalam dunia penerbangan memegang peranan penting dalam keselamatan para penumpang selama berada dalam pesawat. Terjadinya peristiwa penggunaan salah satu narkoba oleh pilot sangat mengejutkan dunia penerbangan. Penggunaan narkoba oleh pilot tentu bukanlah hal yang dapat ditoleransi, karena tanggung jawab pilot atas keselamatan ratusan penumpang. Dalam upaya mewujudkan keselamatan penerbangan yang menyeluruh, diperlukan pengkajian terhadap pengawasan bentuk kesehatan yang selama ini menjadi dasar bagi penilaian kesehatan pilot. Analisis dilakukan secara deskriptif dan hasil analisis menunjukkan bahwa belum tersedianya bentuk pengawasan kesehatan yang efektif bagi pilot jika hanya mengandalkan peran pemerintah sebagai regulator untuk menjamin seluruh keselamatan penerbangan, diharapkan dukungan dari semua pihak, baik itu pemerintah, swasta, masyarakat serta para pelaku penerbangan itu sendiri.